Adjuvant therapy with Huatan Sanjie Granules improves the prognosis of patients with primary liver cancer: a cohort study and the investigation of its mechanism of action based on network pharmacology - Yuan, Juhua; Abdurahman, Abdusami; Cui, Ning; Hao, Tengteng; Zou, Jianhua; Liu, Liren; Wu, Yu (Frontiers in Pharmacology, 2023)
Objective: Nowadays, primary liver carcinoma (PLC) is one of the major contributors to the global cancer burden, and China has the highest morbidity and mortality rates in the world. As a well-known Chinese herbal medicine (CHM) prescription, Huatan Sanjie Granules (HSG) has been used clinically for many years to treat PLC with remarkable efficacy, but the underlying mechanism of action remains unclear. Methods: A clinical cohort study was conducted to observe the overall survival of PLC patients with vs. without oral administration of HSG. Meanwhile, the BATMAN-TCM database was used to retrieve the potential active ingredients in the six herbs of HSG and their corresponding drug targets. PLC–related targets were then screened through the Gene Expression Omnibus (GEO) database. The protein–protein interaction (PPI) network of targets of HSG against PLC was constructed using Cytoscape software. The cell function assays were further carried out for verification. Results: The results of the cohort study showed that the median survival time of PLC patients exposed to HSG was 269 days, which was 23 days longer than that of the control group (HR, 0.62; 95% CI, 0.38–0.99; P = 0.047). In particular, the median survival time of Barcelona Clinic Liver Cancer stage C patients was 411 days in the exposure group, which was 137 days longer than that in the control group (HR, 0.59; 95% CI, 0.35–0.96; P = 0.036). Meanwhile, the enrichment analysis result for the obtained PPI network consisting of 362 potential core therapeutic targets suggest that HSG may inhibit the growth of liver cancer (LC) cells by blocking the PI3K-Akt/MAPK signaling pathways. Furthermore, the above prediction results were verified by a series of in vitro assays. Specifically, we found that the expressions TP53 and YWHA2, the targets of the hepatitis B virus signaling pathway, were significantly affected by HSG. Conclusion: HSG shows promising therapeutic efficacy in the adjuvant treatment of PLC.